Isolation of an insulin-like growth factor II cDNA with a unique 5' untranslated region from human placenta. - Shen, S J (1988)
Human insulin-like growth factor II (IGF-II) cDNA from a placental library was isolated and sequenced. The 5' untranslated region (5'-UTR) sequence of this cDNA differs completely from that of adult human liver and has considerable base sequence identity to the same region of an IGF-II cDNA of a rat liver cell line, BRL-3A. Human placental poly(A)+ RNA was probed with either the 5'-UTR of the isolated human placental IGF-II cDNA or the 5'-UTR of the IGF-II cDNA obtained from adult human liver. No transcripts were detected by using the 5'-UTR of the adult liver IGF-II as the probe. In contrast, three transcripts of 6.0, 3.2, and 2.2 kilobases were detected by using the 5'-UTR of the placental IGF-II cDNA as the probe or the probe from the coding sequence. A fourth IGF-II transcript of 4.9 kilobases presumably containing a 5'-UTR consisting of a base sequence dissimilar to that of either IGF-II 5'-UTR was apparent. Therefore, IGF-II transcripts detected may be products of alternative splicing as their 5'-UTR sequence is contained within the human IGF-II gene or they may be a consequence of alternative promoter utilization in placenta.